Pendeta Za'ba dalam kenangan (Kuala Lumpur Dewan Bahasa dan Pustaka, 2000)
Biography of Zainal Abidin bin Ahmad, Malaysian intellectual.
Includes bibliographical references and index.
Keywords: Za°ba, -- Pendita -- 1895-1973.; Intellectuals -- Malaysia -- Biography; Malaysia -- Biography